2023
DOI: 10.3390/pharmaceutics15030934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhalation Profile on Delivery of Treprostinil Palmitil Inhalation Powder

Abstract: Treprostinil palmitil (TP), a prodrug of treprostinil, is being developed as an inhalation powder (TPIP) for the treatment of patients with pulmonary arterial hypertension (PAH) and pulmonary hypertension due to interstitial lung disease (PH-ILD). In ongoing human clinical trials, TPIP is administered via a commercially available high resistance (HR) RS01 capsule-based dry powder inhaler (DPI) device manufactured by Berry Global (formerly Plastiape), which utilizes the patient’s inspiratory flow to provide the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Since FDA approval, several formulations of treprostinil have been developed, including inhalation and capsule-based dry powder inhaler (DPI) devices 48. DPI devices, similar to well-known devices for asthma and COPD, could enhance patients’ comfort and thus improve compliance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since FDA approval, several formulations of treprostinil have been developed, including inhalation and capsule-based dry powder inhaler (DPI) devices 48. DPI devices, similar to well-known devices for asthma and COPD, could enhance patients’ comfort and thus improve compliance.…”
Section: Discussionmentioning
confidence: 99%
“…DPI devices, similar to well-known devices for asthma and COPD, could enhance patients’ comfort and thus improve compliance. It has been demonstrated that even with lower inhaled volumes and peak inspiratory flows, the administration of fine particles is acceptable 48 49. Moreover, a new pro-drug formulation, treprostinil palmitate, has recently been tested, resulting in fewer AEs and a more sustained effect 48 49…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation